The cardioprotective effects of secoisolariciresinol diglucoside (flaxseed lignan) against cafeteria diet-induced cardiac fibrosis and vascular injury in rats: an insight into apelin/AMPK/FOXO3a signaling pathways - Abdelwahab, Azza H.; Negm, Amira M.; Mahmoud, Eman S.; Salama, Rania M.; Schaalan, Mona F.; El-Sheikh, Azza A. K.; Ramadan, Basma K. (Frontiers in Pharmacology, 2023)
Fast food is a major risk factor for atherosclerosis, a leading cause of morbidity and mortality in the Western world. Apelin, the endogenous adipokine, can protect against cardiovascular disease via activating its receptor, APJ. Concurrently, secoisolariciresinol diglucoside (SDG), a flaxseed lignan extract (FLE), showed a therapeutic impact on atherosclerosis. The current study aimed to examine the effect of SDG on cafeteria diet (CAFD)-induced vascular injury and cardiac fibrosis via tracking the involvement of the apelin/APJ pathway. Thirty male rats were allocated into control, FLE-, CAFD-, CAFD/FLE-, and CAFD/FLE/F13A-treated rats, where F13A is an APJ blocker. All treatments lasted for 12 weeks. The CAFD-induced cardiovascular injury was evidenced by histological distortions, dyslipidemia, elevated atherogenic indices, cardiac troponin I, collagen percentage, glycogen content, and apoptotic markers. CAFD increased both the gene and protein expression levels of cardiac APJ, apelin, and FOXO3a, in addition to increasing endothelin-1, VCAM1, and plasminogen activator inhibitor-1 serum levels and upregulating cardiac MMP-9 gene expression. Moreover, CAFD reduced serum paraoxonase 1 and nitric oxide levels, cardiac AMPK, and nuclear Nrf2 expression. FLE attenuated CAFD-induced cardiovascular injury. Such effect was This is a provisional file, not the final typeset article reduced in rats receiving the APJ blocker, implicating the involvement of apelin/APJ in FLE protective mechanisms. In conclusion, FLE supplementation abrogated CAFD-induced cardiac injury and endothelial dysfunction in an apelin/APJ-dependent manner.